Cu(II) Coordination Polymer With 1D Chain Structure Based on Pyridine-Carboxylate - Zhu, Baoyong (Asian Journal of Chemistry, 2010)
The pyridine carboxylato-bridged coordination polymers [Cu(pbc)2] (Hpbc = 3-pyrid-3-ylbenzoic acid) has been synthesized by the hydrothermal method and characterized by X-ray single crystal diffraction. The compound [Cu(pbc)2] exhibits a 1D chain structure.